Dulkadiran Tradition as a Medium for Strengthening Spirituality and Social Solidarity: An Empirical Study of a Local Muslim Community in Besuk Bulan Rajab Village - Nurul Hidayah; Benny Prasetiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study explores the Dulkadiran tradition in Besuk Bulan Rajab Village as a medium for strengthening spirituality and social solidarity within the local Muslim community. Dulkadiran, held every Rajab to honor Sheikh Abdul Qadir al-Jilani, embodies spiritual teachings and functions as a communal ritual. The objective of this research is to analyze its cultural-religious meaning, its contribution to community cohesion, and its influence on individual and collective spirituality. Using a qualitative approach, this study applies participatory observation and in-depth interviews with key community members, such as village elders and ritual participants. The findings indicate that Dulkadiran is not merely religious practice, but also a mechanism for reinforcing solidarity through collective participation, including food preparation and event organization. This tradition strengthens cooperation and mutual support through shared worship and food distribution. The novelty of this research lies in highlighting Dulkadiran’s dual role as spiritual practice and social unifier in modern contexts.